(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Of course, every person aims to achieve a certain goal by doing something. Along with this, new language learners who have started to learn English,French, German or any other Eastern languages aim to achieve a certain goal and result by learning these languages. Unfortunately, some language learners make mistakes at this step and face a number of difficulties later in the language learning process.